Potato of foreign breeding varieties’ evalution on resistance to casuative agents of wart Synchytrium endobioticum Schilbersky Percival - Zelya, A.; Zelya, G.; Sonets, T.; Makar, T.; Mykhailyk, M. (Quarantine and plant protection, 2023)
Goal. To evaluate and to choose potato varieties of foreign breeding material resistant to wart for inclusion in the State Register of plant varieties suitable for distribution in Ukraine and improve them into disease sources. Methods. The study involved 5 potatoes varieties of foreign breeding: Mia and Baltic Fire — breeding of company Norica Nordring-Kartoffelzucht und Fermerungs GmbH Gross Lusewitz (Germany); Lady Amarilla and Acoustic breeding of company See Meijer B B (Great Britain); Sensation IPM Potato Group Ltd (Ireland). Evaluation of breeding material for resistance to common 1 (D1) and aggressive pathotypes of potato wart was performed in the laboratory conditions of the Ukrainian Science Research Plant Quarantine Station IPP NAAS on an artificial infectious background according to EPPO Standard PM 7/28/1 and EPPO Standard PM 7/28 / 2 and «Methods for evaluation and selection of breeding material for potatoes resistant to wart Synchytrium endobioticum (Schilb.) Perc., Harmonized with EU requirements» and in the field conditions of pathogen spread. Results. As a result of laboratory and field studies on the evaluation and selection of potato varieties resistant to wart were chosen resistant from 5 potato varieties (100%) received value resistant to common potato wart pathotype One variety Acoustic is (20%)resistant to 11(M1) — Mizhgirya aggressive pathotype. There were chosen two resistant varieties to 13 (R2) — Rachiv aggressive pathotype — Sensation and Acoustic; 18(Ya) Yasynya — Acoustic and Lady Amarilla; 22(B1) — Bystrets pathotypes: Sensation and Mia. It was consisted to 40% from general number of testing varieties. Potato variety Baltic Fire defeated by all aggressive potato wart causative agent pathotypes. Conclusions. Potato varieties that have not been affected by the pathotypes of the wart causative agent have been proposed for inclusion in the State Register of Plant Varieties Suitable for Distribution in Ukraine for Introduction. They recommend to put into production in the sources of disease spread and breeders for the following usage in crossing as a source of resistance and receiving resistant against disease potato progenies.